Bio-nematicides Processing from Chicken Manure Waste Enriched with Trichoderma sp Fungi in Pangkalan Gelebak Village - Purwanti, Yani; Nunilahwati, Haperidah; Nisfuriah, Laili; Zairani, Fitri Yetty (Universitas Muhammadiyah Palembang, 2021)
The negative impact of using synthetic pesticides is harmful to health and damaging the environment. Pesticide residues can endanger health and reduce the competitiveness of agricultural products. The use of pesticides includes synthetic nematicides being suppressed or even avoided. One alternative to nematode control that is safe for health and environmentally friendly is bionematicide in organic chicken manure enriched with Trichoderma sp. Production of bio nematicides is an option to be applied by the farmer. This method of making bio nematicides uses simple technology, is practical, inexpensive, and easy to do at the farm level. In addition, the manufacture of this bionematicide will increase the benefits of chicken manure waste. This Community Service Activity that carried out in Pangkalan Gelebak Village, Rambutan District, Banyuasin Regency, on May 6, 2020. The result of this activity is that the farmers are very enthusiastic and motivated to make bionematicide. The bio nematicide produced is expected to control root-knot nematodes on cultivated plants to increase crop production and reduce dangerous synthetic pesticides. Bio nematicide uses are free from toxic pesticides, safe for health, more environmentally friendly, and will ultimately improve the welfare of farmers